Dividend policy and market share price of listed industrial goods companies in Nigeria - Uche , Michael Ugochukwu; Awa, Felix N.; Elom, Joseph Ogwu; Okwu, Peter Ifeanyi (Goodwood Publishing, 2025)
Purpose: The study examined the effect of dividend policy on market share price of listed industrial goods companies in Nigeria. Dividend policy was measured using dividend per share, dividend yield, and dividend payout ratio. Methodology/approach: The study adopted an ex-post facto research design. Data were sourced from audited financial reports of nine sampled industrial goods companies listed in Nigeria, covering the period 2014–2023. The hypotheses were tested using Panel Pooled Regression Analysis with White cross-section standard errors and covariance. Results/findings: Findings revealed a positive and significant effect of dividend per share (p=0.0000) and dividend payout ratio (p=0.0339) on market share price, while dividend yield (p=0.0007) exerted a negative but significant effect. Dividend policy variables jointly explained about 78% of the variation in market share price, indicating their strong explanatory power. Conclusions: The study concluded that proper dividend policy increases the market share price of listed industrial goods companies. Managers and boards should strive to achieve a steady increase in dividend per share, as it enhances market value, but without undermining firm sustainability. Limitations: The study focused only on listed industrial goods companies in Nigeria, which limits the generalizability to other sectors or unlisted firms. Contribution: This research contributes to the literature by providing empirical evidence on the contrasting effects of dividend policy components on share prices in an emerging economy context. By covering a recent ten-year period, it offers fresh insights into how dividend signals are interpreted differently by shareholders, thereby supporting the design of sector-specific financial strategies.